In Situ Spectroscopic Diagnosis of CO 2 Reduction at the Pt Electrode/Pyridine-Containing Electrolyte Interface - Xue-Jiao Chen (317744); Yi-Meng Chen (9971833); Song Yu (3073554); Teng-Xiang Huang (1525426); Shuifen Xie (1631680); De-Yin Wu (1313961); Zhong-Qun Tian (1313955) (2021)
One of the most effective tactics to develop highly efficient catalysts for a CO 2 electroreduction (CER) reaction is by modifying foreign atoms, clusters, and/or molecules to an electrocatalyst surface/interface to break the linear scaling relationship of this complex reaction. Therefore, the report of selective methanol production from a pyridine-mediated CER reaction at the Pt electrode/electrolyte interface triggered extensive attention, which brought about many investigations along this direction and some of them were record-makers. Although promising, the question whether and how pyridine can mediate the CER process is still under tremendous debate. Here, in this work, by virtue of the highly interfacial-sensitive electrochemical surface-enhanced Raman spectroscopy (EC-SERS), we systematically studied the CER process at the Pt electrode/pyridine-containing electrolyte interface. The spectral results showed that pyridine and pyridinium (the protonated pyridine) can interact with the Pt electrode in two ways. One was the chemically adsorbed pyridine molecule (Py) and α-pyridyl radical (α-Pyl) at the first layer, which directly bound to the Pt surface. The other was the physisorbed pyridine and pyridinium at the second layer, which interacted with the chemisorbed Py and α-Pyl adlayer through the van der Waals interaction. The dissolved CO 2 , instead of being steadily reduced, can just be irreversibly transformed into the adsorbed CO, which was a “poison” to the Pt electrode and can seize a large number of binding sites from Py and α-Pyl. The predominant way of CO 2 participating in the electrochemical process was the hydrogen evolution reaction (HER) arising from reducing the carbonic acid. Although the interfacial pyridine species were inert to the CER, the second-layer pyridinium, which was enriched near the electrode in a CO 2 -saturated solution at negative potentials, can mediate HER by playing a role as a proton relay. With the explicit electrochemical interface model established in this work, we can fundamentally explain why pyridine and pyridinium cannot mediate the CER reaction with a Pt electrode from a molecular perspective. Our work provides a viable illustration to explore the interfacial structure, molecular functionality, and even the reaction mechanism of catalytic systems including but not limited to the pyridine-mediated CER at electrochemical interfaces.